Образи суду та судочинства у творах письменників Західної України кінця ХІХ - початку ХХ ст. як об'єкт філософсько-правового аналізу - Павлусів, Н.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматриваются образы суда и судопроизводства в художественной литературе Западной Украины конца XIX - начала XX в. Предлагаемое исследование способно обогатить философско-правовую науку новыми фактами национальной правовой культуры, на основании которых можно формулировать положения о правовом менталитете украинского народа. Делается выывод, что в художественной литературе исследуемого периода отсутствуют действительно положительные образы суда. The article deals with the problem of images of court in the fiction of Western Ukraine of the end of XIX and beginning of XX centuries. This investigation is supposed to enrich philosophy of law with new facts of national legal culture as a fundamental basis for provisions concerning legal mentality of Ukrainian people. The conclusion is done that the fiction of the period mentioned above doesn't represent really positive images of law.